A circular polarization survey for radio stars with the Australian SKA Pathfinder. Issue 4 (5th February 2021) - Pritchard, Joshua; Murphy, Tara; Zic, Andrew; Lynch, Christene; Heald, George; Kaplan, David L; Anderson, Craig; Banfield, Julie; Hale, Catherine; Hotan, Aidan; Lenc, Emil; Leung, James K; et al.
ABSTRACT: We present results from a circular polarization survey for radio stars in the Rapid ASKAP Continuum Survey (RACS). RACS is a survey of the entire sky south of δ = +41 ○ being conducted with the Australian Square Kilometre Array Pathfinder telescope (ASKAP) over a 288 MHz wide band centred on 887.5 MHz. The data we analyse include Stokes I and V polarization products to an RMS sensitivity of 250  μ Jy PSF −1 . We searched RACS for sources with fractional circular polarization above 6 per cent, and after excluding imaging artefacts, polarization leakage, and known pulsars we identified radio emission coincident with 33 known stars. These range from M-dwarfs through to magnetic, chemically peculiar A- and B-type stars. Some of these are well-known radio stars such as YZ CMi and CU Vir, but 23 have no previous radio detections. We report the flux density and derived brightness temperature of these detections and discuss the nature of the radio emission. We also discuss the implications of our results for the population statistics of radio stars in the context of future ASKAP and Square Kilometre Array surveys.